2019
DOI: 10.1177/0731121418820035
|View full text |Cite
|
Sign up to set email alerts
|

Democracy and Infant Mortality in Less-Developed Nations: Dismantling Differences in Direct and Indirect Effects Modeling

Abstract: In recent years, many studies have focused on examining the relationship between democracy and health outcomes in developing nations. However, the overwhelming majority of this research utilizes direct-effect modeling approaches, assuming that increases in democracy are going to directly translate into improvements in well-being. Drawing on a sample of 136 less-developed nations, I first conduct a basic regression, where I find no significant impact of democracy on infant mortality. I then utilize structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Over the past decades, scholarly understanding of the democracy and health relationship seemed to be quite solidified as a plethora of empirical scholarship found that democracy exerts a beneficial effect on health outcomes (e.g., Besley and Kudamatsu 2006; Frey and Al-Roumi1999; Klomp and De Haan 2009; Lake and Baum 2001; Lena and London 1993; London and Williams 1990; Moon and Dixon 1985; Tsai 2006; Wickrama and Mulford 1996; Wigley and Akkoyunlu-Wigley 2011; Young 1990; Zweifel and Navia 2000). A growing body of scholarship challenges our scholarly understanding of the effects of democracy on health outcomes in comparative international context (Burroway 2012, 2016; Noble 2019; Ross 2006; C. L. Shandra et al 2012; Swiss et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, scholarly understanding of the democracy and health relationship seemed to be quite solidified as a plethora of empirical scholarship found that democracy exerts a beneficial effect on health outcomes (e.g., Besley and Kudamatsu 2006; Frey and Al-Roumi1999; Klomp and De Haan 2009; Lake and Baum 2001; Lena and London 1993; London and Williams 1990; Moon and Dixon 1985; Tsai 2006; Wickrama and Mulford 1996; Wigley and Akkoyunlu-Wigley 2011; Young 1990; Zweifel and Navia 2000). A growing body of scholarship challenges our scholarly understanding of the effects of democracy on health outcomes in comparative international context (Burroway 2012, 2016; Noble 2019; Ross 2006; C. L. Shandra et al 2012; Swiss et.…”
Section: Discussionmentioning
confidence: 99%
“…Much scholarship finds that democracy exerts a beneficial effect on health outcomes and social welfare outcomes more broadly (Besley and Kudamatsu 2006; Frey and Al-Roumi 1999; Klomp and De Haan 2009; Lake and Baum 2001; Lena and London 1993; London and Williams 1990; Moon and Dixon 1985; Tsai 2006; Wickrama and Mulford 1996; Wigley and Akkoyunlu-Wigley 2011; Young 1990; Zweifel and Navia 2000). A growing body of scholarship, however, has somewhat eroded confidence in our scholarly understanding of the relationship between democracy and health outcomes in comparative international context (Burroway 2012, 2016; Noble 2019; Ross 2006; C. L. Shandra, Shandra, and London 2012; Swiss et al 2012; Weede 1993; Wejnert 2008).…”
mentioning
confidence: 99%
“…All models include the natural logarithm of real GDP per capita (PPP). Economic development is a common control variable in cross-national research (e.g Clark 2008;Noble 2019)…”
mentioning
confidence: 99%
“…Trade openness I include a measure of Trade Openness, which is commonly measured as trade (exports + imports) as a percentage of GDP (ln) (e.g., Clark 2008;Noble 2019;Sommer, Restivo, and Shandra 2020;Tester 2020). I log-transform this variable to account for skew.…”
Section: Urbanizationmentioning
confidence: 99%